2021
DOI: 10.1186/s40359-021-00684-6
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between dental anxiety and other kinds of anxiety: a naturalistic, cross-sectional and comparative study

Abstract: Background Dental anxiety is of public health importance because it leads to postponed dental treatment, which comes with health complications. The present study investigated whether there is a correlation between the degree of dental anxiety and other kinds of anxiety and whether there are prognostic factors for the different kinds of anxiety. Method In the sample (N = 156) from a dental practice in a large German city, 62% of patients received a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 30 publications
(37 reference statements)
0
11
0
Order By: Relevance
“…This finding is in line with results from the UK and Korea, showing that individuals with higher levels of both general or specific self-efficacy report lower levels of DA [ 22 , 24 ]. However, a recent study from an urban German population found that higher levels of general self-efficacy were not associated with DA but with generalized anxiety [ 21 ]. Nevertheless, the results related to oral health self-efficacy in this context indicate that individuals’ thoughts and perceptions about self-confidence and control related to oral health behaviors and procedures are important factors in determining how individuals cope with stressful situations in dentistry [ 53 ] and that the intervention might have had some influence over these parameters.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This finding is in line with results from the UK and Korea, showing that individuals with higher levels of both general or specific self-efficacy report lower levels of DA [ 22 , 24 ]. However, a recent study from an urban German population found that higher levels of general self-efficacy were not associated with DA but with generalized anxiety [ 21 ]. Nevertheless, the results related to oral health self-efficacy in this context indicate that individuals’ thoughts and perceptions about self-confidence and control related to oral health behaviors and procedures are important factors in determining how individuals cope with stressful situations in dentistry [ 53 ] and that the intervention might have had some influence over these parameters.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, higher knowledge levels are found to be associated with problem-oriented coping, self-management, and self-efficacy among diverse patient groups [ 17 , 18 , 19 ]. Self-efficacy is defined as the expectations or beliefs individuals have about their ability to perform a behavior [ 20 ], and it has been shown that general self-efficacy is associated with lower levels of general anxiety [ 21 ] and dental anxiety [ 22 ]. Though general self-efficacy does not always appear related to DA [ 23 , 24 ], specific types of self-efficacy, e.g., “oral health self-efficacy,” might be more reliably associated with DA, as this concept may prevent and reduce DA for some people [ 21 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…43,44 Moreover, the painful and damaging experience of dentistry, especially conditional experiences during childhood in the dental settings, and observational learning via observing fear of pain by family members are the other factors causing this anxiety. 45 Various studies have investigated the relationship between dental anxiety and pain perception. 46,47 In a study, Sanikop et al (2011) investigated the relationship between dental anxiety and pain perception during scaling.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, it has been shown that OHRQoL was indirectly associated with oral health knowledge through both self-efficacy and DHB [ 14 ]. Furthermore, a negative correlation between OH-SE and DF/A has been reported [ 15 ]. This finding is particularly relevant considering the detrimental effects of DF/A on oral health [ 16 18 ], as it has been shown that DF/A leads to a notable reduction in DHB, which is assumed to contribute to a vicious cycle of aggravated oral health and increased DF/A [ 19 22 ].…”
Section: Introductionmentioning
confidence: 99%